Penerapan Transtheoretical Theory Dan Reintegrative Shaming Theory Terhadap Rehabilitasi Dan Reintegrasi Sosial Bnnp Ntt - Bara, Fadjar; Tallo, Daud Dima; Amalo, Heryanto (Law Faculty, Nusa Cendana University, 2024)
This study examines the Restorative Justice system in BNNP NTT, particularly focusing on the rehabilitation of drug addicts. Issues such as stigma, labeling, limited social support, mental health challenges, and post-rehabilitation job access constraints are identified. By integrating the Transtheoretical Model Theory and Reintegrative Shaming Theory, the research delineates six stages of behavior change at the Rehabilitation Center of BNNP NTT. Recommendations include enhancing education, social support, and collaboration. The research methodology employed is normative research, meaning it involves an examination of relevant laws and other legal sources. Primary legal materials, secondary legal materials, and tertiary legal materials are utilized. Social reintegration can be improved through effective awareness campaigns via social media and community activities. In conclusion, BNNP NTT needs to intensify efforts to support the Restorative Justice System, emphasizing education, social support, and collaboration to enhance the rehabilitation of drug addicts.